Features of grain drying using solid fuel furnace blocks - S. A. Pavlov; A. N. Dadyko (Сельскохозяйственные машины и технологии, 2017)
The urgent tasks in agriculture are fuels alternative types use for grain drying and development of drying technical means, including furnace devices on plant refuse. The drying mode with the increasing temperature of the drying agent is considered as optimum for wet seed grain. Therefore, grain continuously variable temperature increase of the drying agent from initial to finite is used during warming up of a fire chamber. At the beginning the fire chamber is kindled by means of a liquid or gas torch, then solid fuel is given. In the furnace unit in case of submission of solid fuel of primary and secondary blasting there are cyclonic and vortex circuits in which solid particles circulate. When using of plant refuse as fuel the particles are dried and ignite, warming up of a fire chamber and the agent of drying which comes to a heater and to the dryer begins. The drying agent at the same time warms up a fire chamber and dries up grain which circulate in the dryer at the same time. On reaching standard humidity the dryer is transferred to a flow. The authors suggested to use for calculation of drying duration mathematical models of heating and cooling of a fire chamber on the basis of a heat balance and change of an enthalpy of the furnace camera. At the same time the first batch of grain is dried up in case of the ascending temperature condition along with warming up of a fire chamber. Combination of warming up of a fire chamber with grain drying o allows to lower fuel expenses by 15-20 percent as warming up of the furnace unit takes 1-1,5 hours. When drying the last batch of grain the descending mode is carried out. Along with cooling of a fire chamber there is a drying of grain at step-down temperature. Drying duration should be calculated on classical formulas. At the same time temperature of the agent of drying is accepted as average taking into account heat-up the fire chamber and the heat exchanger. The last batch of grain should be dryed up in case of the descending temperature condition. Process duration is defined by temperature of the dried-up material and the mode of cooling of a fire chamber. When calculating the expenditure of solid fuel we should consider costs of heat not only of grain drying, but also of warming up of a fire chamber that is function of thermotechnical parameters of a fire chamber and the dryer.